Intergroup contact, outgroup knowledge and advantaged group collective action: can who you know and what you know promote social change? - Ferry, Caitlin; MacInnis, Cara; Buliga, Elena (Frontiers in Social Psychology, 2024)
Some groups in society unjustly hold greater social, economic, and political power over others, placing some groups in more advantaged and others in more disadvantaged positions. One way to challenge group-based inequality and promote social change is through collective action (e.g., protests, petitions, advocating). Most often, disadvantaged group members engage in collective action. However, when advantaged group members engage in solidarity-based collective action, it can heighten a movement's momentum. Four motivators of collective action among advantaged (and disadvantaged) group members have been identified: identification with the cause, anger about injustice, morality, and group efficacy. We examined what precedes these motivations regarding White Canadians' collective action benefitting Indigenous communities and White Americans' collective action benefitting Black communities. We examined two potential antecedents of advantaged group collective action motivation, intergroup contact and knowledge about the outgroup. In both samples, intergroup contact and knowledge of the outgroup were consistently indirectly associated with collective action through identification with the cause as well as through identification with the cause and anger about injustice. Of the multiple forms of intergroup contact and knowledge examined, the strongest associations were observed for higher quality contact and knowledge of systemic racism. These results have implications for both theory and intervention. Number of words: 11,994 Number of figures: 4 Number of tables: 3 (main text), 8 (supplementary materials)The language style used is British English